Evaluating Chris Argyris's ideas: an Islamic perspective - Fontaine, Rodrigue Ancelot Harvey; Oziev, Gapur; Hassan-Hussein, Hussein (Emerald Group Publishing Limited, 2012)
Purpose – The purpose of this paper is to investigate Chris Argyris's ideas from an Islamic perspective.